The complete chloroplast genome of Hemerocallis Fulva. Issue 2 (3rd July 2019) - Lee, Junki; Lim, Jong-Sung; Kim, So-Yeon; Chun, Hyang Sook; Lee, Dongho; Nah, Gyoungju
Abstract: We have sequenced the complete chloroplast genome of Hemerocallis fulva, a species of the Asphodelaceae family, through Illumina HiSeq paired-end sequencing. The total size of chloroplast genome of Hemerocallis fulva was 155, 855 bp with a large single-copy (LSC) region of 84, 607 bp, a small single-copy (SSC) region of 18, 508 bp, and a pair of identical inverted repeat regions (IRs) of 26, 370 bp. The genome contained a total of 112 genes, including 79 protein-coding genes, 29 transfer RNA (tRNA) genes, and 4 ribosomal RNA (rRNA) genes. The phylogenetic analysis of Hemerocallis fulva with 10 related species exhibited the closest taxonomical relationship with Aloe species in the Asphodelaceae family.